Analysis of Obstacles to Resolving Civil Service Disputes at the Yogyakarta Administrative Court - Aufa, Muhammad Fikri; Widodo, Andrea Brilianto (Strata Law Review, 2025)
Following the enactment of Law Number 5 of 2014 concerning the State Civil Apparatus (ASN), the Yogyakarta State Administrative Court (PTUN) has become a forum for civil servants to defend their legal interests and seek justice. Under this law, a civil servant must first exhaust administrative channels as mandated by Article 129. Specifically, to file a lawsuit with the Yogyakarta PTUN, a civil servant must first file an administrative objection. This step is a prerequisite for the dispute to fall under the court's authority. This research employs a normative legal methodology, using legal analysis that treats law as a system of norms. This system includes principles, ethics, regulations from statutes, court decisions, agreements, and legal doctrines. The study identifies six factors that hinder the resolution of civil servant disputes at the Yogyakarta PTUN. It demonstrates that the challenges in settling these administrative conflicts are influenced not only by the parties involved but also by judges, the nature of the verdicts, and socio-cultural variables.